Effect of the Application of Chlorella Vulgaris Ointment to the Number of Fibroblast Cells as an Indicator of Wound Healing in the Soft Tissue of Pig Ears - Edy Machmud; Muhammad Ruslin; Rahmat Waris; Rustan Ambo Asse; Andi Muamar Qadafi; Harun Achmad (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2022)
Objective: To analyze the clinical and histological condition of Chlorella vulgaris ointment extract smearing on wound healing. Material and Methods: The sample consisted of 9 pigs by making 4 incisions on the pig's right ear measuring 2cm x 1cm and applying Chlorella vulgaris ointment in 3 concentrations namely 5%, 10%, 15% and without ointment application as the control group. Furthermore, the observation of the clinical condition of wounds divided into 4 time periods (day 1, 3, 7 and 14). After completing clinical observations based on time period, the skin of the pig's ear was taken by cutting in the area that had been made injured. Skin tissue extraction carried out under inhalation and local anesthesia. The tissue pieces are then processed in the anatomical pathology laboratory to become 36 slide preparations. The clinical trial assessment was done using parameters of wound moisture, color of wound and scab wound. Whereas for histological examination was done by looking at the number of fibroblast cells in the CX31 light microscope with 40x magnification. ANOVA and Kruskal Wallis tests were used. Results: In the clinical observation conditions there were significant differences between the treatment group and the control group as well as the number of fibroblast cells there were significant differences between the 3 concentrations of Chlorella vulgaris extract ointment and the per time period control group. Conclusion: Chlorella vulgaris extract ointment containing 15% extract gives the best results in accelerating the wound healing process in the pig's ear seen from wound healing and increased number of fibroblast cells.